STRATEGIC MANAGEMENT AS A TOOL FOR CREATING LONG-TERM BUSINESS VALUE - ARTEMENKO, Lina; RYZHIKOVA, Natalia; LAGODIIENKO, Vladislav (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The essence, content and key features of strategic management are explored in the article. New factors influencing the company's activities in a strategic perspective were also investigated here. The current system of factors was supplemented from the standpoint of modern business practices and the achievement of strategic competitive advantages. It is proposed to consider the strategy as a road map for achieving the company's long-term goals and objectives. Two basic methodological approaches to strategic business management are analyzed: process and system. According to modern strategic priorities and goals, both approaches should focus on creating long-term sustainable business development goals. The main advantages formed by strategic management for the development of the company are outlined. It was determined that the composition of traditional strategic management tools (planning and forecasting methods, strategic analysis methods, modeling methods) should now be supplemented with the following: corporate organizational culture, strategic business communications, social responsibility of business.It has been proven that strategic values should be the priority of modern business development strategies. The key values for companies are: people, personnel, partnership relations with stakeholders, preservation of the environment, satisfaction of the interests of all participants in the business process. The modern practice of strategic management of companies should be based on the basic principles of the global concept of sustainable development. The practice of activities of well-known global companies has shown that taking into account the goals and objectives of sustainable development in strategic management contributes to the growth of long-term competitive potential and the realization of one's own business goals. In the context of foreign experience, the main strategic models of the business behavior of companies on the market, which are oriented towards the creation of long-term values, were investigated. Among the factors of successful implementation of the company's strategy, the human factor is identified as the main one. The system of principles of strategic leadership, necessary for the implementation of the process of strategic management of the company, is proposed here.
Keywords: strategic management; business; long-term values; sustainable development; strategic management priorities; management tools; companies